5 Stereotactic treatments on standard accelerator: From implementing technique to treatment patient. (December 2018) - Bertrand, P.; Corbice, C.; Fontaine, E.; Encaoua, J.; Bednarek, C.; Delattre, E.
Abstract : Introduction: Since 2015, the radiotherapy department of Reunion Island university hospital treats patients under stereotactic conditions on standard accelerators equipped with on-board imaging. We started our treatments under stereotactic intracranial in VMAT technique. In 2017, we implemented the 4D option with RPM material (Varian) on our scan and treated patients under extra-cranial stereotactic using dynamic arc therapy. Today, we routinely treat patients for stereotactic head, lung and bones localisation. This work provides a description of the implementation of this practice. Methods: Our results concern 29 patients treated for intracranial stereotactic, 8 with tumor lung and 6 with bone metastasis. The Acuros AXB algorithm is defined as a reference for the intracranial and the AAA algorithm for extra-cranial treatments (1 mm resolution grid). The minimum jaw size we allow is 2x2cm 2 . We evaluate our dosimetry (calculated on Varian's TPS Eclipse) according to the RTOG criteria, conformity and homogeneity indices, and tracking of OARs dose: R100, R50, RCI, CIp and GI indices. We also note the maximum dose 2 cm from PTV in any direction, percent of lung receiving 20 Gy for pulmonary tumors and percent of healthy brain receiving 12 Gy for intracranial stereotactic treatment. A mechanical quality control (QC) is performed, and, before each treatment, a patient QC is realized (Octavius 4D phantom SRS array PTW). Therefore, for each treatment session, CBCT imaging is acquired. Results: For all patients the values (mean ± SD) of R100, R50, RCI, CIp and GI are 1, 18 ± 0, 16; 4, 93 ± 0, 90; 0, 99 ± 0, 01; 0, 83 ± 0, 09 and 4, 14 ± 0, 81 respectively. The mechanical precision tolerances (monthly controls) of linear accelerator are 1 mm per jaw size and 1 mm for isocenter (arm, collimator, table and OBI (kV and CBCT)). The results of gamma index for QC patients are 93.4% ± 10 (local dose 1 mm/ 3–5% with cut off at 50%). Conclusions: Dosimetric indices and QC indicators are satisfactory. By now, our service can offer stereotactic intra and extra-cranial treatment on standard accelerator for patients who lives in Reunion island.